The distribution and population ecology of semaphore crab Ilyoplax sayajiraoi Trivedi, Soni, Trivedi and Vachhrajani 2015, on mud flat region of Gulf of Khambhat, Gujarat, India - Gargi K. Vaidya; Kauresh D. Vachhrajani (Journal of Fisheries, 2021)
The semaphore crab Ilyoplax sayajiraoi is a newly discovered species distributed in the Gulf of Khambhat, Gujarat, India. Consequently, almost no information is available regarding its population structure. The distribution of species is limited to upper most reaches of the gulf and thus any alteration in the habitat will eventually affect its population. Studies on the population structure of I. sayajiraoi will provide baseline data for future studies and probably, it has potential to serve as a bioindicator species. Morphometric measurements of the carapace (width and length), cheliped and body weight were measured for specimens, collected monthly. The growth was not isometric, demonstrating a significant difference in carapace of males and females, giving sexual dimorphism. Relationship established between carapace width and weight indicate that species is allometric in nature. Sex ratio was 1.3 : 1 (M : F).  Ovigerous female and juvenile recruitment showed a bimodal distribution pattern for maintaining the overall size of population.